Pengaruh Model Pembelajaran Complete Sentence Terhadap Keampuan Menulis Surat Dinas Pada Siswa Kelas VII SMPN 1 Pusakajaya - Muliati, Rizka Retno; Sugiarti, Dewi Herlina (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research is motivated by the problems found in the field that students experience difficulties in learning to write official letters, besides that, the application of the learning model has never been applied in writing official letter skills. This affects student learning outcomes to be less than optimal. This study aims to describe student learning outcomes by applying the Complete Sentence learning model in writing official letters to class VII students of SMPN 1 Pusakajaya. This study aims to (1) describe the effect of applying the Complete Sentence learning model in writing official letters for class VII SMPN 1 Pusakajaya, (2) describe student learning outcomes by applying the Complete Sentence learning model in writing official letters to class VII students of SMPN 1 Pusakajaya. This study uses a quantitative approach. The method in this study was a quasi-experimental design with nonequivalent control group design. The correlation between the research design and the purpose of this study is the utilization of the two classes compared before and after receiving treatment. Processing of research data using SPSS software version 25. This research was conducted at SMPN 1 Pusakajaya by taking two classes as samples, namely class 7A and 7C. The sample in this study amounted to 60 students. The research sample was taken by purposive sampling. There are three stages in this study, namely pretest, treatment, and posttest. Based on the results of the study it was found that the average pretest and posttest scores for the experimental class were 52.57 and 84.47, this shows that the pretest and posttest scores had a difference of 31.9. Meanwhile, the average pretest and posttest scores for the control class were 50.85 and 61.14. shows that the two scores have a difference of 10.29. In this case it shows that the score of the experimental class is greater than that of the control class. The research results obtained from the pretest and posttest show that the data is normal and homogeneous. Based on the hypothesis test (T test) on the posttest data results obtained 0.000 <0.05, meaning that Ho is rejected and Ha is accepted. Thus, it was concluded that there was an influence of the Complete Sentence learning model on the ability to write official letters in class VII students of SMPN 1 Pusakajaya.